Extra-Hepatic Portal Venous Obstruction in Pregnant Women of South-Asian Descent: A Case Series - Nimmi Amala; Akshaya Murali; Annamma Thomas (Gynecology Obstetrics & Reproductive Medicine)
Liver diseases complicate approximately 3% of pregnancies worldwide, and require specialized care to ensure optimal pregnancy outcomes. Extra-hepatic portal venous obstruction (EHPVO), even though asymptomatic in a majority of the cases, has a higher risk of variceal bleeding in pregnancy and adverse pregnancy outcomes. In this series, we describe five cases of EHPVO presenting during pregnancy at our tertiary care hospital, their antenatal management, and delivery outcomes. In our case series on EHPVO in pregnancy, a majority of the women were diagnosed during childhood and adequately asymptomatic before pregnancy. Two women underwent Endoscopic band ligation for esophageal varices and one woman underwent splenectomy before pregnancy for disease control. One woman was Anti-nuclear antibody (ANA) positive and another was Anti-phospholipid antibody (APLA) positive, while the other three did not have pre-existing thrombotic tendencies. One patient required Endoscopic band ligation during pregnancy. Pregnancy complicated by hypertension was noted in two of the five women (40%). Four of the five women (80%) had thrombocytopenia requiring blood products during delivery. Two women underwent preterm vaginal delivery, and one woman underwent preterm Caesarean section because of placental abruption. Three women had a post-partum hemorrhage, which was effectively managed with uterotonics and blood products. All five women and their neonates were discharged in good health. Multi-disciplinary approach with standardized antenatal care can give positive pregnancy outcomes in women with EHPVO.